BOOK REVIEW OF THE GUARDIAN WRITTEN BY NICHOLAS SPARKS - Sutopo, Galuh Erawati Agliesta (LANTERN (Journal on English Language, Culture and Literature), 2015)
Book review of The Guardian by Nicholas Sparks is to understand the strengths and weaknesses of The Guardian novel. This analysis uses intrinsic aspects which are theme, character, and setting as analysis focus. The Guardian tells about a journey to find a true love by the main character, Julie Barenson. Although The Guardian has some weaknesses, the strengths of this novel make it still recommended to be read.